2005
DOI: 10.1002/pon.925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the needs and concerns of partners of women at high risk of developing breast/ovarian cancer

Abstract: This exploratory study investigates the experience of partners of women at high risk of developing breast/ovarian cancer and reports on the partners' views concerning their relationship, communication, future planning, children and childbearing, involvement in decision-making regarding screening and prophylactic measures, and information and support needs. In-depth interviews were conducted with 15 partners. Of these, seven were partners of women who were BRCA1/2 mutation carriers, five were partners of women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
60
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 27 publications
5
60
2
Order By: Relevance
“…This finding is consistent with the qualitative findings of our previous study, 11 and another survey study, that investigated the role of relationship communication on the distress levels of women undergoing genetic testing and their partners and found that greater comfort sharing concerns about the genetic testing experience at baseline was associated with lower levels of cancer-specific distress 6 months post-testing among partners. 5 We additionally found that the occurrence of a breast/ovarian cancer-related event in the women's family during the past year was associated with lower levels of general distress for partners.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with the qualitative findings of our previous study, 11 and another survey study, that investigated the role of relationship communication on the distress levels of women undergoing genetic testing and their partners and found that greater comfort sharing concerns about the genetic testing experience at baseline was associated with lower levels of cancer-specific distress 6 months post-testing among partners. 5 We additionally found that the occurrence of a breast/ovarian cancer-related event in the women's family during the past year was associated with lower levels of general distress for partners.…”
Section: Discussionsupporting
confidence: 91%
“…It further predicts that the effects of the mediating units will be moderated by attentional style, with individuals with a tendency to monitor for threatening information (high monitors) likely to experience greater perceived risk than low monitors. 12 In addition, our previous qualitative investigations 11 identified possible couple factors associated with partners' adjustment, and, based on these findings, it is predicted that better adjustment (lower general and cancerspecific distress) for partners will be associated with (i) feeling adequate in providing support to their wives, (ii) greater involvement in decision making, (iii) the perception that their wives are coping well, (iv) agreement between the woman and her partner about cancer-related issues, including satisfaction with the management of her risk, (v) having a team approach, and (vi) communicating openly about this issue. A secondary aim of this study is to explore the association between partners' and women's adjustment.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…As has been reported previously [16], the family member most likely to be named as having read the materials given to the participant during their consultation and having contributed to the genetic testing decision-making process was the participant's spouse or partner. These data again emphasize the importance of considering the spouse within the familial cancer setting, even though they are not blood relatives of the patient [36,37]. Consistent with previous research, there was neither evidence of an effect of the decision aid on women's psychological functioning, genetic testing decisions, scores of informed choice nor their scores on the certainty and feeling supported subscales of the DCS [21,38].…”
Section: Discussionsupporting
confidence: 80%
“…These data support recent research emphasizing the importance of considering the spouse within the familial cancer setting, despite the fact that they are not blood relatives of the patient and therefore not at increased cancer risk themselves. 30 The possible sex differences in the effectiveness of the DA warrant further discussion. Traditionally, research has reported that men have a less positive attitude toward health-related issues in general and toward genetic counseling and testing for hereditary cancer syndromes specifically.…”
Section: Discussionmentioning
confidence: 99%